Luis Emilio RecabarrenEducator of the Chilean Working Class - Maria Alicia Vetter (Adult Education Research Conference, 2015)
This paper is based on a philosophical and historical inquiry into the educational vision of Luis Emilio Recabarren, a working-class leader and organizer of the early 20th century in Chile.
Keywords: working-class education; Chile; history of adult education; social movement learning